Influence of high temperature on dairy productivity of Ukrainian Schwyz - Vasilenko, Tatyana; Василенко, Тетяна Олександрівна; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, Roman; Милостивий, Роман Васильович; Kalinichenko, Alena; Калиниченко, Олена Олександрівна; Gutsulyak, Ganna; Гуцуляк, Ганна Сергіївна; Sazykina, Elisaveta; Сазикіна, Єлизавета Михайлівна (Львівський національний університет ветеринарної медицини та біотехнологій ім. С. З. Ґжицького, 2018)
In monitoring studies of recent years, global warming is reported. This is a significant problem for dairy farming in much of Europe, especially in the central and southern regions, as reported by numerous studies. Dairy cattle highly productive are extremely sensitive to hot temperatures; their consequence is health problems, a significant reduction in milk yield and milk quality. Unfortunately, heat stress remains an unrecognized problem for domestic cattle breeding, although the financial losses from its harmful influence in European are quite substantial. The aim of our work was to study the effect of high temperatures on milk yield of cows of Ukrainian Schwitz on one of the complexes of high-tech milk production. At the beginning of the research, we decided to test the hypothesis of increasing hot air temperatures in the warm period of the year compared with the long-term data. Then we studied how the milk of Schwitz breed varies during the hot season, depending on the magnitude of the maximum temperature values. According to the results of the study, it can be noted that the air temperature during the warm period of 2017 tended to increase (+0.6 ° С) in comparison with the long-term data. In August, the air temperature significantly exceeded the long-term data by +3 ° C (td = 2.89, P<0.05). The relationship between the temperature and milk yield of cows is revealed by an average degree of reliability (r = -0.45, P<0.05). Compared with the most favorable external conditions in May, the cows' milk yield decreased in June by 3.0%, the yield of milk fat by 5.2%, the milk protein content by 3.4% (P<0.001). In July and August, the cows' milk yield decreased by 4.6 and 5.5% (P<0.001), the yield of milk fat decreased by 3.1 and 7.3% (P<0.01-0.001), the yield of milk protein 3.4 and 5.7% (P<0.001). Thus, high temperatures during the summer period contributed to a decrease in milk yield and the main components of milk of the Ukrainian Schwitz, which can lead to tangible financial losses. У моніторингових дослідженнях останніх років повідомляється про глобальне потепління клімату. Це є суттєвою проблемою для молочного тваринництва більшої частини Європи, і особливо для центральних і південних регіонів, про що повідомляють численні дослідження. Високопродуктивна молочна худоба вкрай чутлива до спекотних температур. Їх наслідком є проблеми зі здоров'ям, значне зниження рівня надоїв та якості молока. На жаль, тепловий стрес залишається невизнаною проблемою для вітчизняного скотарства, хоча фінансові втрати від його згубного впливу в європейських країнах досить відчутні. Метою нашої роботи було вивчити вплив високих температур на молочну продуктивність корів швіцької породи на одному з високотехнологічних комплексів з виробництва молока. На початку досліджень нами було вирішено перевірити гіпотезу щодо зростання спекотних температур повітря в теплий період року в порівнянні з багаторічними даними. Ми вивчили, як змінюється удій корів швіцької породи в жаркий період року залежно від величини максимальних значень температур. За результатами дослідження встановлено, що температура повітря в теплий період 2017 року мала тенденцію до зростання (+0,6 ° С) в порівнянні з багаторічними даними. При цьому, в серпні температура повітря достовірно перевищувала багаторічні дані на 3 ° С (P <0,05). Зв'язок між температурою і удоєм корів був достовірним (r = -0,45; P <0,05). У порівнянні з найбільш сприятливими зовнішніми умовами в травні, у червні удій корів зменшувався в на 3,0%, вихід молочного жиру на 5,2%, вміст молочного білка на 3,4% (P<0,001). У липні і серпні у корів удій зменшився на 4,6 і 5,5% (P <0,001), вихід молочного жиру зменшився на 3,1 і 7,3% (P <0,01-0,001), вихід молочного білка 3,4 і 5,7% (P <0,001). Таким чином, високі температури в літній період спричиняли зниженню удою і основних компонентів молока швіцької породи, що може призводити до відчутних фінансових втрат.
Вплив високих температур на молочну продуктивність корів швіцької породи в Україні
Keywords: global warming; глобальне потепління; hot temperatures; спекотні температури; cows; корови; Schwitz breed; швіцька порода; milk yield; вихід молока; yield of milk fat and protein; вихід молочного жиру та білка